CYTOTOXICITY AND HEMOLYTIC ACTIVITIES FROM ULVA.SP SEAWEED EXTRACT - B.Srimathi, Dr. Abirami Arthanari (Chelonian Research Foundation, 2023)
INTRODUCTION: Seas and oceans represent a big store for beneficial algae. It is a real fact that the importance of marine organisms as a source of new substances growing.Seaweeds are the eukaryotic organisms that live in salty water and recognized as a potential source of bioactive natural products.The present review is focusing on the following topic Cytotoxicity and hemolytic activities from ulva.sp seaweed extract AIM:To study the Cytotoxicity and hemolytic activities from ulva.sp seaweed extract MATERIALS AND METHODS: Preparation of crude extract from ulva species seaweed extract.Seaweed samples will be collected from a suitable coastal location, and proper preparation methods will be employed to ensure the preservation of its chemical integrity. RESULTS: The ulva.sp sea weed extract have the crucial role in cytotoxic and hemolytic activity.The cytotoxic activity from ulva sp.sea weed extract have the potential to decrease the cell viability.when the sample concentration increases the hemolytic activity also increases hence the hemolytic activity of ulva species sea weed extract have the potential to increases the hemolytic activity DISCUSSION: The exploration of Ulva sp.seaweed extracts as potential sources of bioactive compounds for anticancer drug development.The observed cytotoxic and hemolytic activities of Ulva sp. seaweed extracts may be attributed to their bioactive constituents, such as polysaccharides, polyphenols, proteins, and peptides KEY WORDS: Ulva species ,Sea weed ,Cytotoxic activity ,Hemolytic activity ,Marine organism,Bioactive compounds